KARAKTERISTIK KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Clara Selviana (Jurnal Akuntansi, 2020)
The purpose of this study is to examine the characteristics of the audit committee on the timeliness of financial reporting on manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016 - 2018. The characteristics of the audit committee are measured by several variables, namely the ability of the Audit Committee’s accounting / financial competence, the number of people in the Committee Audit, Audit Committee meeting frequency, and Proportion of Independent Commissioners. A total of 112 companies went public, which are listed on the Indonesia Stock Exchange (IDX) as samples and have been selected by purposive sampling criteria. The results of this study indicate that: the ability of accounting / financial competence, and the frequency of the number of meetings significantly positive effect on the timeliness of financial reporting. The number of people in the audit committee, and the Independent Commissioner did not have a significant positive effect on the timeliness of financial reporting. Keywords: audit committee, financial reporting, independent commissioner